J.E. Bernier and the historical record. (26th October 2016) - MacEachern, Alan
ABSTRACT: In the 1920s, Canada developed and promoted a sector claim to the Arctic archipelago based on the 1880 transfer from Great Britain and on subsequent occupation, as expressed in licensing, patrols, and posts. The fact that in July 1909 the government-sponsored explorer J.E. Bernier had claimed the sector by planting a flag, indeed, the fact that Canada had him planting flags at all, complicated if not contradicted this narrative. This research note shows that Canadian government officials of the 1920s misunderstood or, more likely, deliberately mischaracterised Bernier's earlier sovereignty work, and in doing so have distorted our historical understanding of it. The note also argues that, contrary to recent writing in this journal, it is likely that Bernier did not make an earlier sector claim in August 1907.